Fuzzy simple hierarchy analysis for supplier selection decision / Zamali Tarmudi...[et al.] - Tarmudi, Zamali; Yusri, Muhammad Yassar; Arunah, Nor Siti Khadijah; Mohamad Khalid, Rusnani (UiTM Cawangan Johor, 2019)
Supplier selection problem usually involves so many ambiguity components and multi-criteria factors consideration towards achieving more precision decision. Different researchers have various approaches to overcome such problem concern. In this paper, the Fuzzy Simple Hierarchy Analysis (FSHA) was proposed to deal with the ambiguity or vague multi-criteria evaluation process which commonly exists in supplier selection decision. The technique is equipped with the linguistic variables, the so-called linguistic hedges (i.e., dilation and concentration) for decision-makers (DMs) to evaluate the criterion with ease and direct to the attributes based on their expertise and/or experiences. To show the applicability and practicality of the proposed method, the related hypothetical example was adopted. The calculation results show that the proposed method is highly beneficial and offers a unique advantage to deal with the diversified and too ill-defined in terms of input criterion. Therefore, a simple and systematic manner in evaluation process can be derived from the proposed method without loss any information.